2011
DOI: 10.1002/hed.21914
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of voice quality in patients with early glottic cancer after transoral laser microsurgery

Abstract: Background We conducted longitudinal voice evaluations in patients with early glottic cancer who underwent transoral laser microsurgery (TLM) to determine the time to stability. Methods Twenty‐five patients underwent TLM, including 13 limited cordectomies (type I and type II) and 12 extended cordectomies (type III to type IV). Multidimensional voice evaluations were performed before treatment and at 1, 3, 6, and 12 months after treatment. Results Voice parameters of asthenicity, strain, mean airflow rate (MFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 33 publications
(49 reference statements)
10
61
2
Order By: Relevance
“…In the literature, vocal parameters after type I and type II cordectomy were not significantly different from those of normal controls [17,26]. Other studies reported that type I and type II cordectomies provided better voice quality than did type III to type V excisions [19,27,28]. …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the literature, vocal parameters after type I and type II cordectomy were not significantly different from those of normal controls [17,26]. Other studies reported that type I and type II cordectomies provided better voice quality than did type III to type V excisions [19,27,28]. …”
Section: Discussionmentioning
confidence: 94%
“…The minimum follow-up period from the completion of treatment to voice quality evaluation was set at 6 months since voice quality usually becomes stable after 6 months [18,19]. Voice quality was evaluated 6-12 months after completion of each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We also carried out evaluations at 1 month after surgery. Since in the literature (22) it has been shown that the best assessment of the postoperative results can be obtained at the 6 th month, we considered as results of this study the data obtained at the 6 th month evaluations. In the present study, we have also included specific correlations between subjective and objective tools.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this technique is that it can be easily repeated in case of histologically proven positive or uncertain resection margins. [13] In this study, we determined that using radiofrequency ablation, excision of small lesions (T 1a-b ) in early stage laryngeal carcinomas damages the tissue and so commenting on these tissues in histopathological evaluation is difficult. However, cauterization with radiofrequency gives uncertain margins in the remaining surgical zone compared with conventional surgery.…”
Section: Discussionmentioning
confidence: 99%